Bone mineral density in comparison to anthropometric parameters and level of gross motor function in children with cerebral palsy - Zvekić-Svorcan Jelena; Stojšić Mirjana; Krasnik Rastislava; Nenadov Nataša; Demeši-Drljan Čila; Mikov Aleksandra; Radovanov Maja (Vojnosanitetski Pregled)
Background/Aim. Children with cerebral palsy (CP) grow at a slower rate relative to their peers. Their body height, body weight and bone mineral density are significantly below those measured for healthy children of corresponding age. The aim of this work was to estimate bone mineral density in relation to the anthropometric parameters and the level of gross motor function in the children with cerebral palsy. Methods. This cross-sectional pilot study included 23 children with CP, aged 6 to 17 years, in whom the gross motor function level was estimated according to the Gross motor function classification system- expanded and revised (GMFCS-E&R), while the anthropometric parameters were established in relation to the developmental charts for healthy children as well as those pertaining to children with CP. Bone mineral density was measured by dual energy X-ray absorptiometry and the findings were interpreted in accordance with the International Society for Clinical Densitometry Official Positions of Adults & Pediatrics. Mean values with interquartile deviations, along with frequencies and percentages were the descriptive statistical measures employed in the analyses. Differences between groups were ascertained through the Kruskal-Wallis test. Results. Our sample of 23 children comprised of 56.5% boys and 43.5% girls, aged 13.00 ± 3.56 years, of whom 3/4 had a severe form of gross motor dysfunction (GMFCS-E&R levels IV and V). All subjects had lower bone density in both regions of interest [spinal Z-score -1.60 ± 1.40 standard devation (SD); hip Z-score -2.00 ± 3.00 SD], as well as lower anthropometric parameters [height Z-score -2.74 ± 4.28; body weight Z-score - 3.22 ± 6.96; body mass index (BMI) Z-score -2.64 ± 6.03]. In the observed sample, bone mineral density in the spine (p < 0.01) and the hip (p < 0.05) was reduced in all subjects, and all children had a lower body weight (p < 0.01) and the BMI (p < 0.01), but not body height, in relation to the existing developmental charts for the CP children adopted from the US. Children with the CP Level IV on the GMFCS-E&R had a significantly lower bone density (spinal Z-score -1.90 SD; hip Z-score -3.40 SD), with the reduction even more pronounced at level V (spinal Z-score -3.80 SD; hip Z-score -2.30 SD). Conclusion. A significantly lower bone mineral density as well as the decreased values of all observed anthropometric parameters, were noted in the children with CP. In the observed sample, bone mineral density in both spine and hip was reduced in all subjects, all of whom also had lower body weight and the BMI, but not body height compared to the existing developmental charts for the children with CP adopted from the US. The children with severe forms of CP (GMFCS-E&R levels IV and V) had significantly lower bone mineral density.